Unsteady boundary layer flow of a micropolar fluid near a stagnation point with uniform suction or injection - Lok, Yian Yian (Penerbit UTM Press, 2007)
This paper studies the effect of suction or injection on unsteady bounday layer flow of a micropolar fluid near the forward stagnation point of a permeable wall. The velocity of the external flow as well as that of suction or injection are assumed to start impulsively from rest and are maintained thereafter. The model is governed by a set of coupled partial differential equations that is solved numerically for some values of the suction, injection and material parameters. Profiles for the velocity, microrotation and skin friction coeffiecient are determinedand presented in tables and graphical forms. The results show that suction increases the skin friction while the opposite behaviour is observed for the case of injection. It is also found that an increase in the material parameter will enhance the flow near the wall. On the other hand, it can be seen that in the case of injection, longer time is required to approach the steady flow than in the case of suction